Diminished Progression of Periapical Lesions with Zoledronic Acid in Ovariectomized Rats - Wayama, Marcelo Tadahiro [UNESP]; Yoshimura, Hitoshi; Ohba, Seigo; Yoshida, Hisato; Matsuda, Shinpei; Kobayashi, Junichi; Kobayashi, Motohiro; Gomes Filho, João Eduardo [UNESP]; Sano, Kazuo (Elsevier B.V., 2015)
Introduction: The aim of this study was to investigate the effects of systemically administered zoledronic acid (ZOL) on the progression of periapical lesions in estrogen-deficient rats. Methods: Female Wistar rats were divided into the following groups: SHAM-veh, sham surgery treated with vehicle (physiological saline); OVX-veh, ovariectomy treated with vehicle; SHAM-ZOL, sham surgery treated with ZOL; and OVX-ZOL, ovariectomy treated with ZOL. Vehicle or ZOL was administered intravenously once a week for 4 weeks. The pulp of the mandibular first molar of all rats was exposed to the oral environment to induce a periapical lesion, and the lesions were analyzed after 7 and 30 days. The mandibles were examined by micro-computed tomographic imaging and histopathologic, histometric, and immunohistochemical analyses. Results: Histopathologically, the OVX-veh group had more severe inflammation and bone loss and a larger number of cells that were positive for tartrate-resistant acid phosphatase compared with the SHAM-veh and OVX-ZOL groups; the SHAM-veh and OVX-ZOL groups were similar to each other. The SHAM-ZOL group had the lowest magnitude of these conditions. Tomographically, the OVX-veh group had greater bone loss than the other groups at both time points. The SHAM-veh, SHAM-ZOL, and OVX-ZOL groups had similar bone loss at both time points. In the sagittal section on day 30, the SHAM-ZOL group had lower bone loss compared with the SHAM-veh and OVX-ZOL groups. Conclusions: The hypoestrogenic condition aggravates the progression of periapical lesions. ZOL therapy may help contain bone destruction of periapical lesions.
Keywords: Bisphosphonate; estrogen deficiency; osteonecrosis